Transformational Leadership Style of Village Heads in Facing the Digital Era (Case Study: Cimenyan Village, Cimenyan District, Bandung Regency) - Pius Suratman Kartasasmita; Firdaus, Rasya; Tutik Rachmawati (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
Transformational leadership plays a crucial role in addressing contemporary leadership challenges. When applied by the village chief, this leadership style directs the village towards a more modern and sustainable future. This study aims to examine the leadership style of village chiefs in facing the digital era through a case study in Cimenyan Village, a high-achieving village in West Java. The research employs a qualitative approach with data collection techniques including interviews, observations, and document studies, and utilizes thematic analysis with Atlas.ti 24.1 software. The research findings conclude by adopting the concept of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The study shows that the village chief of Cimenyan applies transformational leadership concepts in his work. The chief successfully realizes vision and mission statements, builds harmonious relationships, enhances the quality of public services, and effectively utilizes technology and human resources for the progress of Cimenyan Village.